ELECTION CAMPAIGNS IN THE REPUBLIC OF KAZAKHSTAN AND FORMATION AND DEVELOPMENT OF TECHNOLOGIES - Boltabaev Bakhtiyor Sabirjonovich (The Conference Hub, 2025)
In this article, the electoral system of the Republic of Kazakhstan, the laws adopted on elections are expressed in their content essence, the implementation of electoral processes of local self-government bodies.
Keywords: Constitution of the Republic of Kazakhstan, election laws, decrees, main candidates in elections, Socialist Party of Kazakhstan, people's Congress of Kazakhstan, Union of people's unity of Kazakhstan, civil movement “Azad”, Republican social movement “Lad” Local Self-Government bodies, socio-political associations.